STRATEGI PENINGKATAN KOMPETENSI APARATUS NEGARA MELALUI METODE COACHING DAN MENTORING DI RUMAH SAKIT UMUM DAERAH KABUPATEN BANGKA - Nashafi, Ahmad Hafiduddin; Hidayat, Wahyu (Universitas Panca Marga, 2023)
At present, developing the competence and quality of apparatus resources in all fields has become a necessity in both the public and private sectors. Human resource (HR) development has become the focus of government reform, especially the State Civil Apparatus (ASN) as a very important HR asset for the development of a country. This study aims to determine the Strategy for Improving the Competence of the State Civil Apparatus (ASN), both partially and jointly, through coaching and mentoring at the Bangka Regency Hospital. The data used in this study is data that shows that coaching and mentoring are practices that effectively encourage our drive to improve our self-worth, problem-solving skills, and confidence in handling challenges. The targets set in the coaching and mentoring plan can be achieved well. In addition, the success of coaching is how a coachee discovers his/her potential and utilizes it and the success of mentoring is how a coachee is able to apply what his/her mentor teaches independently and utilize his/her potential.